Edmodo use in ESP writing: The perceptions and barriers of sociology students - Fu'ad Sholikhi (English Language Teaching Educational Journal, 2020)
The teachers are expected to integrate technology into the classroom because today is the world of a computer. Edmodo is one of the educational websites that can facilitate the specific needs of Sociology students in writing. This research aimed to investigate the second-semester Sociology students perceive the use of Edmodo as a medium in writing descriptive text and how Edmodo helps the students in developing their writing skills. Qualitative research was used by researchers through documentation, observation, and interviews with twelve Sociology students as participants at Islamic University of Balitar. This study took eight months to complete the analysis which included data reduction, display of the data, and analysis of Sociology students’ data. The result showed that Edmodo was helpful in ESP class (writing class) because Edmodo enhanced Sociology students’ writing, developed interaction, communication, and it promoted Sociology students’ creativity in solving the writing task. The analysis of the result suggested that further researchers research motivation or behavior stages because this research only focused on the perception stage. Further researchers also suggested that further researchers revise the research instruments.